Analysis of Developing Anti-Corruption Education in Indonesia Through Media-Based Citizenship Education Learning Smart Mobile Civic - Trisiana, Anita; Priyanto, Anang; Sutoyo, Sutoyo (Jurnal Cakrawala Pendidikan, 2024)
The purpose of this study is to analyze the development of anti-corruption education in Indonesia, through learning Citizenship Education based on Smart Mobile Civic media. Efforts to eradicate corruption are not only the responsibility of law enforcement agencies or the government, but also the responsibility of all components of the nation. Therefore, efforts to eradicate corruption must be carried out by involving all relevant stakeholders, namely the government, the private sector and the community. This research method uses a qualitative approach. The use of qualitative methods in research can produce a more comprehensive study of a phenomenon. The results of the study show that: Citizenship Education learning system has a very strategic role, to increase students' understanding of anti-corruption education. In this context of research, the students, as agents of corruption prevention, cannot be separated from the characteristics they possess, such as: Intellectuality, Youth Spirit, and Idealism. Student involvement in the anti-corruption movement can basically be divided into four areas: within the family, on campus, in the local community, and at the regional or national level. The digital era has had a tremendous impact on citizenship learning, such as through the application of Smart Mobile Civic media as a fun and not boring learning media for students so that they can explore more deeply about their knowledge and experiences.